Complete revascularization of multivessel coronary artery disease in patients with ST elevation acute coronary syndrome - for whom and when? A comprehensive review - Spacek, Miloslav; Vacha, Jan; Precek, Jan; Hutyra, Martin; Nykl, Radomir; Sluka, Martin; Taborsky, Milos (Biomedical papers, 2023)
Atherosclerosis is the most common cause of coronary steno-occlusive disease and acute myocardial infarction is the leading cause of death in industrialized countries. In patients with acute ST elevation myocardial infarction (STEMI), there is unquestionable evidence that primary percutaneous coronary intervention providing recanalization of the infarct related artery (IRA) is the preferred reperfusion strategy. Nevertheless, up to 50% of patients with STEMI have multivessel coronary artery disease defined as at least 50% stenosis exclusive of IRA. There is conflicting data regarding the optimal treatment strategy and timing in such patients. Currently, it is assumed that stable patients might benefit from complete revascularization particularly in reducing the need for future unplanned procedures but only culprit lesion should be treated during index procedure in unstable patients. In this article, we provide a comprehensive overview of this important and currently highly debated topic.
Keywords: atherosclerosis; acute ST elevation myocardial infarction (STEMI); multivessel coronary artery disease (CAD); infarct related artery (IRA); complete revascularization; coronary flow; fractional flow reserve (FFR)